Impact of Foreign Direct Investment on Renewable Energy Generation: Evidence from Europe - Korani, Amirmohammad Esmaeili (International Journal of Energy Economics and Policy, 2025)
Currently, energy production is mainly dependent on fossil fuels and nonrenewable energy. However, reducing the reliance on fossil fuels and employing renewable energy technology is essential for maintaining environmental sustainability and energy security. Despite noteworthy research on foreign financing and renewable energy consumption, few studies have discussed the relationship between foreign direct investment (FDI) and renewable energy generation (REG) that enables such consumption. Thus, this study fills this gap in the literature by applying the generalized method of moments/dynamic panel data (GMM/DPD) estimation technique to determine the impact of FDI on REG in European economies from 2010 to 2022. Based on the results, FDI has a significant and negative impact on REG. The implication of the findings is that policymakers should decide on suitable incentive programs, such as feed-in tariffs, electricity purchase agreements, and renewable project tax credits, in order to redirect FDI from nonrenewable energy sources to the renewable energy sector.